Localization of phosphorylated ErbB1-4 and heregulin in colorectal cancer - Mitsui, Keigo (BMC Cancer, 2014)
BACKGROUND: The ErbB family consists of four proteins including (EGFR)/ErbB1, ErbB2, ErbB3, and ErbB4, and plays a crucial role in the promotion of multiple tumorigenic processes. In addition to the traditional pathways of EGFR signaling, EGFR translocates to the nucleus and acts as a transcription factor in the proliferation of cancer cells. Heregulin is known as both an ErbB3 and an ErbB4 ligand. This study aimed to investigate the expression of heregulin and its relevant EGFR family members as well as their phosphorylated forms in human colorectal cancer (CRC) tissues and to determine the relationship between their expression and clinicopathological factors including patient prognosis. METHODS: We analyzed the effects of exogenous heregulin on ErbB2, ErbB3 and ErbB4 phosphorylation in Caco-2, DLD-1, and HCT 116 colon cancer cell lines by western blot analysis. We examined 155 surgical resections from colorectomy patients. Cellular localization of ErbB1-4, their phosphorylated forms and heregulin protein was analyzed in CRC surgical resections by immunohistochemical analysis. Immunohistochemical results were compared with clinicopathological factors and patient prognosis. RESULTS: Phosphorylated ErbB2 (pErbB2) and phosphorylated ErbB3 (pErbB3) were detected in both nuclear and cytosolic fractions of Caco-2 and DLD-1 cells stimulated by exogenous heregulin. Whereas, phosphorylated ErbB4 (pErbB4) was detected only in cytosolic fractions of HCT 116 cells stimulated by exogenous heregulin. Phosphorylated EGFR (pEGFR) immunoreactivity was observed in the cytoplasm and nuclei of cancer cells, whereas the pattern of EGFR staining was membranous and cytoplasmic. Subcellular localization of pErbB2, cytoplasmic, membranous, or nuclear, varied among cases. pErbB3 immunoreactivity was exclusively observed in the nuclei of cancer cells. pErbB4 immunoreactivity was observed in the cell membrane of cancer cells. Statistically, heregulin immunoreactivity correlated with pErbB2 and pErbB4 expression. In multivariate analysis for disease free survival, lymph node status, pErbB3 and pErbB4 expression retained independent prognostic significance. In multivariate analysis for overall survival, lymph node status, pEGFR and pErbB4 retained independent prognostic significance. CONCLUSIONS: ErbB2 and ErbB3 phosphorylated by heregulin localized in the nucleus of CRC cells. Phosphorylated ErbB1-4 and heregulin contribute to poorer patient prognosis in CRC. This heregulin-ErbB family member autocrine loop may be a candidate for targeted treatment of CRC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2407-14-863) contains supplementary material, which is available to authorized users.